PENGARUH ONLINE CONSUMER REVIEW DAN KUALITAS PRODUK TERHADAP CITRA MEREK DAN KEPUTUSAN PEMBELIAN PADA PRODUK CREAMATTE EMINA DI KOTA PEKANBARU - Fitri Nurul Maghfira; Wijayanto Gatot; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to find out the influence of online consumer review and product quality on brand image and the decision to buy Creamatte Emina in Pekanbaru City. The population of this study is a community in Pekanbaru City who have watched online consumer reviews and have bought Emina Creamatte products. The primary data in the study was obtained from the dissemination of questionnaires as instruments to prove the results of the study as well as to test the proposed hypothesis. This study used structural equation modeling (SEM) analysis method using Warp-PLS software version 6.0. Sampling using the technique of Non Probability Sampling with Purposive Sampling procedure by sampling as many as 170 respondents. The results of this study showed that online consumer review and product quality had a positive and significant effect on brand image and purchasing decisions on emina creamatte products in Pekanbaru City.Keywords : Online consumer review, product quality, brand image, purchasing decision, Creamatte Emina.